A Firenze si producono (ancora) delle straordinarie mappe in rilievo - Bernardini, Fulvio (GEOmedia, 2019)
The Global Map continues the long Florentine cartographic tradition, which is characterized by the ability, the tendency to perfection and the artistic vision but, above all, the passion. Like the one of its general manager Andrea Bonomo, for which the maps are the main instrument of knowledge.